Is activation in inflammatory bowel diseases associated with further impairment of coronary microcirculation?. (15th November 2016) - Caliskan, Zuhal; Keles, Nursen; Gokturk, Huseyin Savas; Ozdil, Kamil; Aksu, Feyza; Ozturk, Oguzhan; Kahraman, Resul; Kostek, Osman; Tekin, Ahmet S.; Ozgur, Gulsum Teke; Caliskan, Mustafa
Abstract: Background: Inflammatory bowel disease [IBD] includes a number of chronic relapsing diseases. In IBD intestinal microvascular endothelial cells are damaged by an abnormal immune response. Several studies have shown that IBD may cause increment in risk of developing atherosclerosis. IBD in activation was related to enhanced risks of worse cardiovascular [CV] outcome, on the other hand no risk increment was seen in remission comparing to control group in those studies. Coronary Flow Reserve [CFR] reflects coronary microvascular circulation. Coronary microvascular dysfunction may be defined as a predictor of CV outcome combined with previous described atherosclerotic risk factors. The present study was purposed to further evaluate whether or not CFR in the left anterior descending artery [LAD] is disturbed in IBD patients with activation in comparison to remission and healthy subjects. Methods: 62 patients with IBD and 39 healthy volunteers were enrolled into the study. Patients' demographics were recorded. CFR evaluation of patients with IBD in both activation and remission period and control group were performed with transthoracic echocardiography. Results: CFR was significantly lowest in the active period of the IBD [2.26 [2.08–2.55] vs. 2.55 [2.18–3.00] and 3.10 [2.85–3.29] p < 0.001]. CFR is negatively correlated with disease activity scores of IBD. Conclusion: This study showed that CFR is more prominently disturbed in patients with IBD in activation. The activation of disease may have a major role in the progression of coronary microcirculatory dysfunction and future cardiovascular events. Highlights: The coronary microcirculation is more prominently impaired in IBD patients throughout active period of the disease. The active inflammation may have a major role in the coronary microvascular dysfunction and future cardiovascular events. Monitoring firmly and suppressing the flare of IBD might improve cardiovascular prognosis in patients with IBD.